STUDI EMPIRIS ATAS DAMPAK KEBIJAKAN KENAIKAN TARIF PPN TERHADAP DAYA BELI MASAYARAKAT DAN INFLASI EKONOMI DOMESTIK - Sari, Intan Purnama; Nofrizal, Nofrizal (Ensiklopedia of Journal, 2025)
This study aims to analyse the impact of the policy to increase the Value Added Tax (VAT) rate from 11% to 12% on people's purchasing power and domestic economic inflation in Indonesia. This policy was implemented in order to increase state revenue, but it has economic consequences that need to be examined empirically. The VAT rate increase directly drives up the prices of consumer goods and services, which can reduce household consumption, especially among low-income groups. In a macroeconomic context, a decline in household consumption — which accounts for more than 50% of gross domestic product (GDP) — has the potential to slow economic growth. In addition, the VAT increase also drives cost-push inflation due to price adjustments at the producer and consumer levels. Using a descriptive approach and empirical literature study, this research finds that even though the rate increase is only 1%, its impact on purchasing power and inflation is quite significant, thus requiring supporting policies to maintain economic stability and protect vulnerable groups.Keywords: VAT, purchasing power, inflation, household consumption, fiscal policy